Aerogel nanoporous A-grade non-combustible thermal insulation board and preparation method thereof

By using aerogel nano-micropore technology and graphene-encapsulated resin structure in non-combustible insulation boards, combined with silicate cement compounding, the problems of insufficient thermal conductivity and hygroscopicity of traditional insulation boards are solved, and efficient insulation performance is achieved and Compressive strength, suitable for building energy conservation needs.

CN118388208BActive Publication Date: 2025-02-21HEBEI TIANMING QIXING PREFABRICATED BUILDING TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410709901.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-03
Publication Date
2025-02-21
Estimated Expiration
2044-06-03

AI Technical Summary

Technical Problem

The existing non-combustible insulation boards have shortcomings in thermal conductivity and hygroscopicity, which is difficult to meet the needs of building energy saving.

Method used

Aerogel nano microporous A-grade non-combustible insulation board is used, and its raw materials include silicate cement, fly ash, polypropylene fibers, polystyrene particles, reinforced graphene, silica sol, etc., and graphene is formed through specific preparation methods. The wrapped resin structure is combined with silicate cement compound to improve curing speed and compressive strength.

Benefits of technology

It realizes the advantages of low thermal conductivity and adjustable bulk weight, overcomes the shortcomings of traditional insulation boards, has excellent insulation performance and compressive strength, and is suitable for insulation systems of building peripheral structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118388208B_ABST
    Figure CN118388208B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of thermal insulation boards, and specifically discloses an aerogel nanoporous Class A non-combustible thermal insulation board, wherein the raw materials include by mass: 50-100 parts of silicate cement, 1-5 parts of fly ash, 1-5 parts of polypropylene fiber, 1-5 parts of polystyrene particles, 5-10 parts of enhanced graphene, 5-15 parts of silica sol, 0.1-1 parts of high-efficiency water reducer, 1-3 parts of quicklime, 1-3 parts of gypsum, 1-2 parts of calcium chloride, 1-2 parts of early strength agent, 1-3 parts of aluminum silicate powder, 1-2 parts of oxidized paraffin, and 0.1-1 parts of polyacrylamide. The present invention also discloses a preparation method of the above-mentioned aerogel nanoporous Class A non-combustible thermal insulation board. The Class A non-combustible thermal insulation board obtained by the present invention integrates light weight, high strength, heat preservation and flame retardant properties, overcomes the respective shortcomings of inorganic expanded perlite thermal insulation board and foamed cement thermal insulation board, has the advantages of lower thermal conductivity and adjustable bulk density, and is suitable for large-scale promotion and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thermal insulation boards, and in particular to an aerogel nano-microporous A-class non-combustible thermal insulation board and a preparation method thereof. Background Art

[0002] In recent years, with the rapid development of my country's economy, urban buildings have brought convenience to people, but also unprecedented threats to people's safety. At this time, the fire resistance of urban buildings has naturally attracted unprecedented attention. As my country attaches great importance to the fire resistance of thermal insulation wall materials, thermal insulation boards with excellent fire resistance are becoming more and more popular.

[0003] At present, non-combustibility has become the basic requirement for insulation boards. Inorganic lightweight aggregate insulation boards with expanded perlite as insulation aggregate have the advantages of excellent flame retardancy, stable physical and chemical properties, long life cycle, and green environmental protection, and have become one of the main directions of wall insulation material development. However, the aggregates of traditional insulation boards, such as expanded perlite, vitrified microspheres, and expanded vermiculite, have high thermal conductivity, generally 0.06-0.07W / (m·K), and strong hygroscopicity, with a mass water absorption rate of about 300%, which is bound to have an adverse effect on the insulation performance of the insulation board; although the foamed cement insulation board has the advantages of low thermal conductivity and small bulk density due to its porous structure, it has the disadvantages of large shrinkage value, high water absorption rate and many cracks, and it is currently difficult to meet the development needs of my country's building energy conservation. Summary of the invention

[0004] The purpose of the present invention is to solve the shortcomings of the prior art and to propose an aerogel nano-microporous A-class non-combustible thermal insulation board and a preparation method thereof.

[0005] The invention discloses an aerogel nano-microporous Class A non-combustible thermal insulation board, wherein the raw materials thereof include, by weight, 50-100 parts of silicate cement, 1-5 parts of fly ash, 1-5 parts of polypropylene fiber, 1-5 parts of polystyrene particles, 5-10 parts of reinforced graphene, 5-15 parts of silica sol, 0.1-1 part of high-efficiency water reducing agent, 1-3 parts of quicklime, 1-3 parts of gypsum, 1-2 parts of calcium chloride, 1-2 parts of early strength agent, 1-3 parts of aluminum silicate powder, 1-2 parts of oxidized paraffin and 0.1-1 part of polyacrylamide.

[0006] Preferably, the strength grade of silicate cement is 42.5.

[0007] Preferably, the high-efficiency water reducer is an aminosulfonate water reducer and / or a polycarboxylate water reducer.

[0008] Preferably, the early strength agent is at least one of sodium sulfate, triethanolamine and triisopropanolamine.

[0009] Preferably, the enhanced graphene is prepared by the following specific steps: lignin and phenol are mixed, stirred at 40-50°C for 1-2h, hexamethylenetetramine, formaldehyde and water are added thereto, hydrothermally reacted at 170-190°C for 1-2h, cooled to 80-90°C, graphene oxide is added thereto and stirred for 5-10h, filtered, washed, vacuum dried, crushed and sieved, immersed in a sodium hydroxide solution with a concentration of 0.1-0.5mol / L, the temperature is adjusted to 5-15°C, immersed for 10-30min, filtered, washed to neutral, and vacuum dried.

[0010] More preferably, the mass ratio of lignin, phenol, hexamethylenetetramine, formaldehyde, water and graphene oxide is 5-10:5-15:1-2:1-3:30-60:5-10.

[0011] The method for preparing the above-mentioned aerogel nano-microporous Class A non-combustible thermal insulation board comprises the following steps:

[0012] S1. Adjust the pH value of silica sol to 5.5-6.2 with hydrochloric acid, add anhydrous ethanol to it under stirring, keep warm at 40-60°C for 5-10h, add enhanced graphene, stir at 70-90°C for 10-20min, let stand for 10-20h, cool to room temperature, wash, and vacuum dry to obtain prefabricated aerogel;

[0013] S2. Add silicate cement, fly ash, polypropylene fiber, and polystyrene particles to the water in a stirring state, mix them evenly, then add prefabricated aerogel, high-efficiency water reducer, quicklime, gypsum, calcium chloride, and early strength agent and stir for 5-15 minutes to obtain a premix;

[0014] S3. Add aluminum silicate powder, paraffin oxide and polyacrylamide to the premix and stir for 5-15 minutes. Let stand at 50-60℃ for 10-40 minutes, pour and cure for 40-60 hours.

[0015] Preferably, in S1, the concentration of hydrochloric acid is 0.1-1 mol / L.

[0016] Preferably, in S3, the curing is first performed in the mold, and then naturally cured indoors after demoulding.

[0017] More preferably, the curing time in the mold is 20-30 hours, and the natural curing time indoors is 20-30 hours.

[0018] Beneficial effects:

[0019] The Class A non-combustible thermal insulation board obtained by the present invention combines light weight, high strength, thermal insulation and flame retardancy, has the advantages of both inorganic expanded perlite thermal insulation board and foamed cement thermal insulation board, overcomes the respective disadvantages of inorganic expanded perlite thermal insulation board and foamed cement thermal insulation board, has the advantages of lower thermal conductivity and adjustable bulk density, and is suitable for large-scale promotion and application.

[0020] The present invention uses lignin to compound with phenol, hexamethylenetetramine and formaldehyde, and forms lignin-based phenolic resin nanoparticles through hydrothermal reaction, and then reacts with graphene oxide and combines with the sheet structure, and further uses sodium hydroxide to corrode the surface of the nanoparticles to obtain a graphene-wrapped resin structure. Compounding with silicate cement can not only effectively accelerate the curing process, but also effectively reduce the shrinkage deformation caused by dehydration and drying, and can effectively reduce cracking.

[0021] The present invention forms silica sol into gel under acidic conditions. After ethanol replacement, the active hydroxyl groups on the network structure can react with active functional groups such as carboxyl groups on the surface of enhanced graphene, which not only greatly improves the networking degree and compressive strength of the skeleton, but also effectively reduces the overall thermal conductivity of the insulation board, and has a good insulation effect.

[0022] The invention has a simple production process, and while reducing the bulk density and replacing part of the cement, it helps to improve the overall compressive strength of the product and is not prone to cracking; at the same time, it improves the mechanical properties and durability, has excellent thermal insulation performance, and expands the scope of use of thermal insulation boards on the market, and is particularly suitable for the thermal insulation system of the building's exterior envelope structure.

[0023] The thermal insulation board obtained by the present invention can reach the Class A standard in GB8624-2012 "Classification of Combustion Performance of Building Materials and Products", and its thermal conductivity reaches 0.024-0.031W / (m·K), with better use effect and stronger adaptability. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a comparison chart of the compressive strength and thermal conductivity of the insulation boards obtained in Example 5 and Comparative Examples 1-2.

[0025] Figure 2 It is a comparison chart of the linear shrinkage of the insulation boards obtained in Example 5 and Comparative Examples 1-2. DETAILED DESCRIPTION

[0026] The present invention will be further explained below in conjunction with specific embodiments.

[0027] Example 1

[0028] The invention discloses an aerogel nano-microporous Class A non-combustible thermal insulation board, whose raw materials include: 50kg of silicate cement PO42.5, 1kg of fly ash, 1kg of polypropylene fiber, 1kg of polystyrene particles, 5kg of reinforced graphene, 5kg of silica sol, 0.1kg of aminosulfonate water reducing agent, 1kg of quicklime, 1kg of gypsum, 1kg of calcium chloride, 1kg of sodium sulfate, 1kg of aluminum silicate powder, 1kg of oxidized paraffin and 0.1kg of polyacrylamide.

[0029] The reinforced graphene is prepared by the following specific steps: 5 kg of lignin and 5 kg of phenol are mixed, stirred at a temperature of 40°C for 1 hour, 1 kg of hexamethylenetetramine, 1 kg of formaldehyde, and 30 kg of water are added thereto, hydrothermally reacted at a temperature of 170°C for 1 hour, cooled to 80°C, 5 kg of graphene oxide is added thereto, stirred for 5 hours, filtered, washed, vacuum dried, crushed, sieved through a 100-mesh sieve, soaked in a sodium hydroxide solution with a concentration of 0.1 mol / L, soaked at a temperature of 5°C for 10 minutes, filtered, washed to neutrality, and vacuum dried.

[0030] The method for preparing the above-mentioned aerogel nano-microporous Class A non-combustible thermal insulation board comprises the following steps:

[0031] S1. The pH value of the silica sol is adjusted to 5.5-6.2 with 0.1 mol / L hydrochloric acid, 5 kg of anhydrous ethanol is added thereto at a stirring speed of 20 r / min, the mixture is kept at 40°C for 5 h, the enhanced graphene is added, the mixture is stirred at 70°C for 10 min, the mixture is allowed to stand for 10 h, the mixture is cooled to room temperature, washed, and vacuum dried to obtain a prefabricated aerogel;

[0032] S2. Add silicate cement, fly ash, polypropylene fiber, and polystyrene particles to 30 kg of water in a stirring state, mix well, and then add prefabricated aerogel, aminosulfonate water reducer, quicklime, gypsum, calcium chloride, and sodium sulfate and stir for 5 minutes to obtain a premix;

[0033] S3. Add aluminum silicate powder, paraffin oxide and polyacrylamide to the premix, stir for 5 minutes, let stand at 50°C for 10 minutes, pour into the insulation board mold for casting, cure in the mold for 20 hours, demould, and naturally cure indoors for 20 hours.

[0034] Example 2

[0035] The invention discloses an aerogel nano-microporous Class A non-combustible thermal insulation board, wherein the raw materials thereof include: 100 kg of silicate cement PO42.5, 5 kg of fly ash, 5 kg of polypropylene fiber, 5 kg of polystyrene particles, 10 kg of reinforced graphene, 15 kg of silica sol, 1 kg of polycarboxylic acid water reducer, 3 kg of quicklime, 3 kg of gypsum, 2 kg of calcium chloride, 2 kg of triethanolamine, 3 kg of aluminum silicate powder, 2 kg of oxidized paraffin and 1 kg of polyacrylamide.

[0036] The reinforced graphene is prepared by the following specific steps: 10 kg of lignin and 15 kg of phenol are mixed, stirred at a temperature of 50°C for 2 hours, 2 kg of hexamethylenetetramine, 3 kg of formaldehyde, and 60 kg of water are added thereto, hydrothermally reacted at a temperature of 190°C for 2 hours, cooled to 90°C, 10 kg of graphene oxide is added thereto, stirred for 10 hours, filtered, washed, vacuum dried, crushed, sieved through a 100-mesh sieve, soaked in a sodium hydroxide solution with a concentration of 0.5 mol / L, soaked at a temperature of 15°C for 30 minutes, filtered, washed to neutral, and vacuum dried.

[0037] The method for preparing the above-mentioned aerogel nano-microporous Class A non-combustible thermal insulation board comprises the following steps:

[0038] S1. The pH value of the silica sol is adjusted to 5.5-6.2 with 1 mol / L hydrochloric acid, 10 kg of anhydrous ethanol is added thereto at a stirring speed of 60 r / min, the mixture is kept at 60°C for 10 h, the enhanced graphene is added, the mixture is stirred at 90°C for 20 min, the mixture is allowed to stand for 20 h, the mixture is cooled to room temperature, washed, and vacuum dried to obtain a prefabricated aerogel;

[0039] S2. Add silicate cement, fly ash, polypropylene fiber, and polystyrene particles to 70 kg of water in a stirring state, mix well, and then add prefabricated aerogel, polycarboxylate water reducer, quicklime, gypsum, calcium chloride, and triethanolamine and stir for 15 minutes to obtain a premix;

[0040] S3. Add aluminum silicate powder, paraffin oxide and polyacrylamide to the premix, stir for 15 minutes, let stand at 60°C for 40 minutes, pour into the insulation board mold for casting, cure in the mold for 30 hours, demould, and naturally cure indoors for 30 hours.

[0041] Example 3

[0042] The invention discloses an aerogel nano-microporous Class A non-combustible thermal insulation board, wherein the raw materials thereof include: 70 kg of silicate cement PO42.5, 4 kg of fly ash, 2 kg of polypropylene fiber, 4 kg of polystyrene particles, 7 kg of reinforced graphene, 12 kg of silica sol, 0.2 kg of aminosulfonate water reducing agent, 2.5 kg of quicklime, 1.5 kg of gypsum, 1.8 kg of calcium chloride, 1.3 kg of triisopropanolamine, 2.5 kg of aluminum silicate powder, 1.3 kg of oxidized paraffin and 0.7 kg of polyacrylamide.

[0043] The reinforced graphene is prepared by the following specific steps: 7 kg of lignin and 12 kg of phenol are mixed, stirred at a temperature of 43°C for 100 min, 1.3 kg of hexamethylenetetramine, 2.5 kg of formaldehyde, and 40 kg of water are added thereto, hydrothermally reacted at a temperature of 182°C for 80 min, cooled to 88°C, 7 kg of graphene oxide is added thereto, stirred for 8 h, filtered, washed, vacuum dried, crushed, sieved through a 100-mesh sieve, soaked in a sodium hydroxide solution with a concentration of 0.2 mol / L, soaked at a temperature of 12°C for 15 min, filtered, washed to neutral, and vacuum dried.

[0044] The method for preparing the above-mentioned aerogel nano-microporous Class A non-combustible thermal insulation board comprises the following steps:

[0045] S1. The pH value of the silica sol was adjusted to 5.5-6.2 with 0.7 mol / L hydrochloric acid, 9 kg of anhydrous ethanol was added thereto at a stirring speed of 30 r / min, the mixture was kept at 45°C for 9 h, enhanced graphene was added, the mixture was stirred at 75°C for 18 min, the mixture was allowed to stand for 12 h, the mixture was cooled to room temperature, washed, and vacuum dried to obtain a prefabricated aerogel;

[0046] S2, under stirring, add silicate cement, fly ash, polypropylene fiber, polystyrene particles to 60kg water in sequence, mix well, then add prefabricated aerogel, aminosulfonate water reducer, quicklime, gypsum, calcium chloride, triisopropanolamine and stir for 8min to obtain a premix;

[0047] S3. Add aluminum silicate powder, paraffin oxide and polyacrylamide to the premix, stir for 12 minutes, let stand at 52°C for 30 minutes, pour into the insulation board mold for casting, cure in the mold for 22 hours, demould, and naturally cure indoors for 27 hours.

[0048] Example 4

[0049] An aerogel nano-microporous Class A non-combustible thermal insulation board, whose raw materials include: 90kg of Portland cement PO42.5, 2kg of fly ash, 4kg of polypropylene fiber, 2kg of polystyrene particles, 9kg of reinforced graphene, 8kg of silica sol, 0.8kg of polycarboxylic acid water reducer, 1.5kg of quicklime, 2.5kg of gypsum, 1.2kg of calcium chloride, 1.7kg of triethanolamine, 1.5kg of aluminum silicate powder, 1.7kg of oxidized paraffin, and 0.3kg of polyacrylamide.

[0050] The reinforced graphene is prepared by the following specific steps: 9 kg of lignin and 8 kg of phenol are mixed, stirred at a temperature of 47°C for 80 minutes, 1.7 kg of hexamethylenetetramine, 1.5 kg of formaldehyde, and 50 kg of water are added thereto, hydrothermally reacted at a temperature of 175°C for 100 minutes, cooled to 82°C, 9 kg of graphene oxide is added thereto, stirred for 6 hours, filtered, washed, vacuum dried, crushed, passed through a 100-mesh sieve, soaked in a sodium hydroxide solution with a concentration of 0.4 mol / L, soaked at a temperature of 8°C for 25 minutes, filtered, washed to neutral, and vacuum dried.

[0051] The method for preparing the above-mentioned aerogel nano-microporous Class A non-combustible thermal insulation board comprises the following steps:

[0052] S1. The pH value of the silica sol was adjusted to 5.5-6.2 with 0.3 mol / L hydrochloric acid, 7 kg of anhydrous ethanol was added thereto at a stirring speed of 50 r / min, the mixture was kept at 55°C for 7 h, enhanced graphene was added, the mixture was stirred at 85°C for 12 min, the mixture was allowed to stand for 18 h, the mixture was cooled to room temperature, washed, and vacuum dried to obtain a prefabricated aerogel;

[0053] S2. Add silicate cement, fly ash, polypropylene fiber, and polystyrene particles to 40 kg of water in a stirring state, mix well, and then add prefabricated aerogel, polycarboxylate water reducer, quicklime, gypsum, calcium chloride, and triethanolamine and stir for 12 minutes to obtain a premix;

[0054] S3. Add aluminum silicate powder, paraffin oxide and polyacrylamide to the premix, stir for 8 minutes, let stand at 58°C for 20 minutes, pour into the insulation board mold for casting, cure in the mold for 28 hours, demould, and naturally cure indoors for 23 hours.

[0055] Example 5

[0056] An aerogel nano-microporous Class A non-combustible thermal insulation board, whose raw materials include: 80kg of silicate cement PO42.5, 3kg of fly ash, 3kg of polypropylene fiber, 3kg of polystyrene particles, 8kg of reinforced graphene, 10kg of silica sol, 0.5kg of polycarboxylic acid water reducer, 2kg of quicklime, 2kg of gypsum, 1.5kg of calcium chloride, 1.5kg of triisopropanolamine, 2kg of aluminum silicate powder, 1.5kg of oxidized paraffin, and 0.5kg of polyacrylamide.

[0057] The reinforced graphene is prepared by the following specific steps: 8 kg of lignin and 10 kg of phenol are mixed, stirred at a temperature of 45°C for 90 minutes, 1.5 kg of hexamethylenetetramine, 2 kg of formaldehyde, and 45 kg of water are added thereto, hydrothermally reacted at a temperature of 180°C for 90 minutes, cooled to 85°C, 8 kg of graphene oxide is added thereto, stirred for 7 hours, filtered, washed, vacuum dried, crushed, sieved through a 100-mesh sieve, soaked in a sodium hydroxide solution with a concentration of 0.3 mol / L, soaked at a temperature of 10°C for 20 minutes, filtered, washed to neutral, and vacuum dried.

[0058] The method for preparing the above-mentioned aerogel nano-microporous Class A non-combustible thermal insulation board comprises the following steps:

[0059] S1. The pH value of the silica sol was adjusted to 5.5-6.2 with 0.5 mol / L hydrochloric acid, 8 kg of anhydrous ethanol was added thereto at a stirring speed of 40 r / min, the mixture was kept at 50°C for 8 h, the enhanced graphene was added, the mixture was stirred at 80°C for 15 min, the mixture was allowed to stand for 15 h, the mixture was cooled to room temperature, washed, and vacuum dried to obtain a prefabricated aerogel;

[0060] S2, under stirring, add silicate cement, fly ash, polypropylene fiber, polystyrene particles to 50kg water in sequence, mix well, then add prefabricated aerogel, polycarboxylate water reducer, quicklime, gypsum, calcium chloride, triisopropanolamine and stir for 10min to obtain a premix;

[0061] S3. Add aluminum silicate powder, paraffin oxide and polyacrylamide to the premix, stir for 10 minutes, let stand at 55°C for 25 minutes, pour into the insulation board mold for casting, cure in the mold for 25 hours, demould, and naturally cure indoors for 25 hours.

[0062] Comparative Example 1

[0063] The invention discloses an aerogel nano-microporous Class A non-combustible thermal insulation board, wherein the raw materials thereof include: 80 kg of silicate cement PO42.5, 3 kg of fly ash, 3 kg of polypropylene fiber, 3 kg of polystyrene particles, 8 kg of graphene oxide, 10 kg of silica sol, 0.5 kg of polycarboxylic acid water reducer, 2 kg of quicklime, 2 kg of gypsum, 1.5 kg of calcium chloride, 1.5 kg of triisopropanolamine, 2 kg of aluminum silicate powder, 1.5 kg of oxidized paraffin and 0.5 kg of polyacrylamide.

[0064] The method for preparing the above-mentioned aerogel nano-microporous Class A non-combustible thermal insulation board comprises the following steps:

[0065] S1. The pH value of the silica sol is adjusted to 5.5-6.2 with 0.5 mol / L hydrochloric acid, 8 kg of anhydrous ethanol is added thereto at a stirring speed of 40 r / min, the mixture is kept at 50° C. for 8 h, graphene oxide is added, the mixture is stirred at 80° C. for 15 min, the mixture is allowed to stand for 15 h, the mixture is cooled to room temperature, washed, and vacuum dried to obtain a prefabricated aerogel;

[0066] S2, under stirring, add silicate cement, fly ash, polypropylene fiber, polystyrene particles to 50kg water in sequence, mix well, then add prefabricated aerogel, polycarboxylate water reducer, quicklime, gypsum, calcium chloride, triisopropanolamine and stir for 10min to obtain a premix;

[0067] S3. Add aluminum silicate powder, paraffin oxide and polyacrylamide to the premix, stir for 10 minutes, let stand at 55°C for 25 minutes, pour into the insulation board mold for casting, cure in the mold for 25 hours, demould, and naturally cure indoors for 25 hours.

[0068] Comparative Example 2

[0069] An aerogel nano-microporous Class A non-combustible thermal insulation board, whose raw materials include: 80kg of silicate cement PO42.5, 3kg of fly ash, 3kg of polypropylene fiber, 3kg of polystyrene particles, 8kg of reinforced graphene, 10kg of silica sol, 0.5kg of polycarboxylic acid water reducer, 2kg of quicklime, 2kg of gypsum, 1.5kg of calcium chloride, 1.5kg of triisopropanolamine, 2kg of aluminum silicate powder, 1.5kg of oxidized paraffin, and 0.5kg of polyacrylamide.

[0070] The reinforced graphene is prepared by the following specific steps: 8 kg of lignin and 10 kg of phenol are mixed, stirred at a temperature of 45°C for 90 minutes, 1.5 kg of hexamethylenetetramine, 2 kg of formaldehyde, and 45 kg of water are added thereto, hydrothermally reacted at a temperature of 180°C for 90 minutes, cooled to 85°C, 8 kg of graphene oxide is added thereto, stirred for 7 hours, filtered, washed, vacuum dried, crushed, sieved through a 100-mesh sieve, soaked in a sodium hydroxide solution with a concentration of 0.3 mol / L, soaked at a temperature of 10°C for 20 minutes, filtered, washed to neutral, and vacuum dried.

[0071] The method for preparing the above-mentioned aerogel nano-microporous Class A non-combustible thermal insulation board comprises the following steps:

[0072] S1. The pH value of the silica sol is adjusted to 5.5-6.2 using 0.5 mol / L hydrochloric acid, 8 kg of anhydrous ethanol is added thereto at a stirring speed of 40 r / min, the mixture is kept at 50° C. for 8 h, allowed to stand for 15 h, cooled to room temperature, washed, and vacuum dried to obtain a prefabricated aerogel;

[0073] S2, under stirring, add silicate cement, fly ash, polypropylene fiber, polystyrene particles, and reinforced graphene to 50kg water in sequence, mix well, then add prefabricated aerogel, polycarboxylate water reducer, quicklime, gypsum, calcium chloride, and triisopropanolamine and stir for 10min to obtain a premix;

[0074] S3. Add aluminum silicate powder, paraffin oxide and polyacrylamide to the premix, stir for 10 minutes, let stand at 55°C for 25 minutes, pour into the insulation board mold for casting, cure in the mold for 25 hours, demould, and naturally cure indoors for 25 hours.

[0075] According to GB8624-2012 "Classification of Combustion Performance of Building Materials and Products", the insulation boards obtained in Example 5 and Comparative Examples 1-2 were tested, and all three were Class A non-combustible products.

[0076] The compressive strength test of the insulation board obtained in Example 5 and Comparative Examples 1-2 was carried out with reference to GB / T 17671-2021 "Test Method for Cement Mortar Strength (ISO Method)"; the thermal conductivity of the insulation board obtained in Example 5 and Comparative Examples 1-2 was measured with reference to GB / T 10297-2015 "Hot Wire Method for Determination of Thermal Conductivity of Non-Metallic Solid Materials". As shown in the following table, and plotted as Figure 1 .

[0077]

[0078] like Figure 1 As shown, the insulation board obtained in Example 5 has the highest compressive strength and the lowest thermal conductivity, and has a better insulation effect.

[0079] The linear shrinkage of the insulation board obtained in Example 5 and Comparative Examples 1-2 was tested with reference to GB / T 20473-2021 "Building Insulation Mortar". As shown in the following table, and plotted as Figure 2 .

[0080]

[0081] like Figure 2 As shown, the thermal insulation board obtained in Example 5 has the lowest linear shrinkage, which can effectively reduce cracking.

[0082] The applicant believes that this is because the present invention uses lignin to compound with phenol, hexamethylenetetramine, and formaldehyde, and after hydrothermal reaction, lignin-based phenolic resin nanoparticles are formed, which then react with graphene oxide and combine with the sheet structure, and further use sodium hydroxide to corrode the surface nanoparticles to obtain a graphene-wrapped resin structure. Its compounding with silicate cement can not only effectively accelerate the curing process, but also effectively reduce the shrinkage deformation caused by dehydration and drying, and can effectively reduce cracking; and the silica sol is formed into a gel under acidic conditions. After ethanol replacement, the active hydroxyl groups on its network structure can react with active functional groups such as carboxyl groups on the surface of enhanced graphene, which not only greatly improves the networking degree and compressive strength of the skeleton, but also effectively reduces the overall thermal conductivity of the insulation board, and has a good insulation effect.

[0083] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. An aerogel nanoporous Class A non-combustible insulation board, characterized in that: The raw materials include, by mass: 50-100 parts of silicate cement, 1-5 parts of fly ash, 1-5 parts of polypropylene fiber, 1-5 parts of polystyrene particles, 5-10 parts of reinforced graphene, 5-15 parts of silica sol, 0.1-1 parts of high-efficiency water reducing agent, 1-3 parts of quicklime, 1-3 parts of gypsum, 1-2 parts of calcium chloride, 1-2 parts of early strength agent, 1-3 parts of aluminum silicate powder, 1-2 parts of oxidized paraffin, and 0.1-1 parts of polyacrylamide; The enhanced graphene is prepared by the following specific steps: lignin and phenol are mixed, stirred at 40-50°C for 1-2h, hexamethylenetetramine, formaldehyde and water are added thereto, hydrothermally reacted at 170-190°C for 1-2h, cooled to 80-90°C, graphene oxide is added thereto and stirred for 5-10h, filtered, washed, vacuum dried, crushed and sieved, immersed in a sodium hydroxide solution with a concentration of 0.1-0.5mol / L, the temperature is adjusted to 5-15°C, immersed for 10-30min, filtered, washed to neutral, and vacuum dried.

2. The aerogel nanoporous Class A non-combustible thermal insulation board according to claim 1, characterized in that: The strength grade of Portland cement is 42.

5.

3. The aerogel nanoporous Class A non-combustible insulation board according to claim 1, characterized in that: The high-efficiency water reducer is aminosulfonate water reducer and / or polycarboxylate water reducer.

4. The aerogel nanoporous Class A non-combustible insulation board according to claim 1, characterized in that: The early strength agent is at least one of sodium sulfate, triethanolamine and triisopropanolamine.

5. The aerogel nanoporous Class A non-combustible thermal insulation board according to claim 1, characterized in that: The mass ratio of lignin, phenol, hexamethylenetetramine, formaldehyde, water and graphene oxide is 5-10:5-15:1-2:1-3:30-60:5-10.

6. A method for preparing the aerogel nanoporous Class A non-combustible insulation board according to any one of claims 1 to 5, characterized in that: The steps include: S1. Adjust the pH value of silica sol to 5.5-6.2, add anhydrous ethanol to it under stirring, keep warm at 40-60°C for 5-10h, add enhanced graphene, stir at 70-90°C for 10-20min, let stand for 10-20h, cool to room temperature, wash, and vacuum dry to obtain prefabricated aerogel; S2. Add silicate cement, fly ash, polypropylene fiber, and polystyrene particles to the water in a stirring state, mix them evenly, then add prefabricated aerogel, high-efficiency water reducer, quicklime, gypsum, calcium chloride, and early strength agent and stir for 5-15 minutes to obtain a premix; S3. Add aluminum silicate powder, paraffin oxide and polyacrylamide to the premix and stir for 5-15 minutes. Let stand at 50-60℃ for 10-40 minutes, pour and cure for 40-60 hours.

7. The method for preparing the aerogel nanoporous Class A non-combustible thermal insulation board according to claim 6, characterized in that: In S1, hydrochloric acid is used to adjust the pH value of the silica sol to 5.5-6.

2.

8. The method for preparing the aerogel nanoporous Class A non-combustible thermal insulation board according to claim 6, characterized in that: The concentration of hydrochloric acid is 0.1-1 mol / L.

9. The method for preparing the aerogel nanoporous Class A non-combustible thermal insulation board according to claim 6, characterized in that: In S3, the curing is first carried out in the mold, and then naturally cured indoors after demoulding.

10. The method for preparing the aerogel nanoporous Class A non-combustible thermal insulation board according to claim 9, characterized in that: The curing time in the mold is 20-30 hours, and the natural curing time indoors is 20-30 hours.

Citation Information

Patent Citations

  • Graphene oxide modified cement-based composite heat-insulating material and preparation method and application thereof

    CN108793880A

  • Class-A incombustible aerogel polyphenyl thermal insulation plate and preparation method thereof

    CN109721312A